2020
DOI: 10.21109/kesmas.v15i4.3811
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Knowledge, Attitudes, and Practices on Rabies in the Philippines

Abstract: In 2007, the Philippine government passed the Anti-Rabies Act to address rabies in the country. However, rabies is still a major public health concern in many provinces. This study aimed to evaluate the knowledge, attitude, and practices (KAP) of residents on rabies, the Anti Rabies Act, and responsible pet ownership (RPO) in Pampanga, Philippines. A cross-sectional survey was done from October 2017 to February 2018 in 92 randomly selected barangays in the province. Questionnaires were adapted from similar stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Another study revealed that lack of awareness and insufficient funds are the primary reasons for not visiting the ABTC [7]. Despite the identified knowledge gaps, there is a consensus among the rabies KAP studies conducted in the Philippines that the population has a relatively good knowledge about rabies and responsible pet ownership [15,19,20].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Another study revealed that lack of awareness and insufficient funds are the primary reasons for not visiting the ABTC [7]. Despite the identified knowledge gaps, there is a consensus among the rabies KAP studies conducted in the Philippines that the population has a relatively good knowledge about rabies and responsible pet ownership [15,19,20].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%